Outreach Effectiveness and Inter-Organizational Coordination as Drivers of Service Quality in a One-Stop Public Service Mall - Fhariz El Habyb; Syamsir Syamsir (Journal of Education on Social Science (JESS), 2026)
One-stop public service malls are designed to reduce citizens’ transaction costs by consolidating multiple services in a single location. Yet early-stage implementation often faces adoption and credibility challenges. This study investigates how outreach effectiveness and inter-organizational coordination shape perceived service quality in a one-stop public service mall in Padang Panjang, Indonesia. Using a single-case qualitative design, the study draws on interviews with key stakeholders, non-participant observation, and document review, analyzed through triangulation and a mechanism-oriented coding scheme. Findings show that outreach is most effective when it functions as citizen preparedness infrastructure, providing standardized, actionable information on requirements, process flows, operating hours, and realistic completion expectations, thereby strengthening assurance before arrival. Coordination affects service quality primarily by producing reliability through multi-tenant operational consistency, including stable staffing, uniform application of standards, synchronized information updates, and rapid problem-solving. Crucially, outreach and coordination are tightly coupled: when outreach raises expectations faster than operational reliability improves, credibility erodes and adoption slows. The study proposes a credibility-first operating model for early-stage one-stop malls, emphasizing a single source of truth for public information, enforceable tenant commitments, daily monitoring with escalation, and closed-loop complaint governance.